2014
DOI: 10.7748/ns2014.01.28.22.37.e7951
|View full text |Cite
|
Sign up to set email alerts
|

Service user involvement in nurse education

Abstract: Service user involvement is now recognised as an integral component of nurse education. This article describes the involvement of one service user, who experienced a traumatic limb amputation, in an educational session for second-year nursing students at De Montfort University. The aim of the initiative was to use the patient's experience to improve care delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 0 publications
0
11
0
1
Order By: Relevance
“…This is reflected in the Midwifery Council (NMC, 2010, 2016) guidance on maintaining the impetus of SUI in nursing education and requiring evidence in courses (NMC, 2011). As service users are regarded as experts through experience (Muir and Laxton, 2012), their involvement can assist in helping students develop skills that will contribute to quality of patient care (Tremayne, et al, 2014) The purpose of SUI in education according to Tew et al (2004) is to be involved across all spectrum of involvement, from consulting to partnership. This would mean involving service users in recruitment of students, curriculum design, delivery and assessment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This is reflected in the Midwifery Council (NMC, 2010, 2016) guidance on maintaining the impetus of SUI in nursing education and requiring evidence in courses (NMC, 2011). As service users are regarded as experts through experience (Muir and Laxton, 2012), their involvement can assist in helping students develop skills that will contribute to quality of patient care (Tremayne, et al, 2014) The purpose of SUI in education according to Tew et al (2004) is to be involved across all spectrum of involvement, from consulting to partnership. This would mean involving service users in recruitment of students, curriculum design, delivery and assessment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Sur le plan international, de nombreuses publications proviennent du Royaume-Uni où l'implication des patients est considérée comme une composante intégrale de l'éducation des infirmières (Lathlean et al, 2006 ;Livingston & Cooper, 2004 ;Tremayne, Russell, & Allman, 2014). En effet, les programmes de formation en sciences infirmières doivent démontrer qu'ils impliquent les patients dans la planification, l'enseignement et l'évaluation du cursus universitaire (Terry, 2013).…”
Section: Méthodeunclassified
“…Service user involvement in health care education programmes is now seen as integral to learning in health education programmes (Tremayne et al 2014, Russel andAllman 2014). The impact is wideranging: studies have found service-user involvement develops knowledge, skills and attitudes (Tremayne et al 2014), promotes commitment to a user-orientated approach (McKutcheon and Gormley 2014), enhances care and narrows the theory-practice gap (Turnbull and and Weeley 2013). Additional benefits include promoting positive realistic attitudes while dispelling preconceptions (Blackhall Shafer and Nightingale 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In the change of role to staff member, the service user becomes 'helper' rather than 'helped', a shift in the power-relationship (Rush 2008) which more accurately reflects the value of service users' opinions and experience (Tremayne et al 2014). Involvement in professional education is often perceived as empowering by service users (McKeown et al 2012, Terry 2013) who value the opportunity to challenge stereotypical views (Simpson et al, 2008) and so influence future practice (Tremayne et al 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation